SNPs of miR-23b, miR-107 and HMGA2 and their Relations with the Response to Medical Treatment in Acromegaly Patients - Armagan, Derya Metin; Akdemir, Ayse Seda; Ozkaya, Hande Mefkure; Korkmaz, Ozge Polat; Gazioglu, Nurperi; Kadioglu, Pinar; Tanriover, Necmettin; Dagistanli, Kaya-Fatma; Dirican, Ahmet; Ozturk, Melek (Experimental and Clinical Endocrinology & Diabetes, 2020)
Introduction Acromegaly is a chronic disease of increased growth hormone (GH) secretion and elevated insulin-like growth factor-I (IGF-I) levels induced by a pituitary adenoma. HMGA2 (high mobility group A2) and AIP (aryl hydrocarbon receptor-interacting protein) expression levels are related to GH-secreting adenomas, and also a response to Somatostatin Analogs (SSAs). We studied SNPs in miR-107 and miR-23b that related with AIP and HMGA2 genes respectively and control their expression, and also SNP in the 3'UTR of HMGA2 gene. Our aim was to investigate genotype distributions of the studied SNPs, as well as the possible relationship between disease and/or response to SSAs treatment in patients with acromegaly.Material and Methods Genotypes were determined by qRT-PCR method from DNA materials obtained blood samples of acromegaly patients (141) and healthy individuals (99). The genotype distributions of patients and healthy groups, as well as the relationship between the clinical data of the disease and genotypes were statistically compared.Results In acromegaly patients with T-allele, p53 expression (p=0.049) was significantly higher. In patients with CT+TT genotype and T-allele who were responder to SSA-treatment Ki-67 index (respectively p=0.019, p=0.020 respectively) was higher. We did not observe the genotypes for miR-23b and miR-107 polymorphisms in the patients and control group of Turkish population.Conclusion The genetic variations of the miRNAs genes related with HMGA2 and AIP genes were not seen in our study. Although there is no relationship between HMGA2-rs1351394 polymorphism and acromegaly disease, T allele was associated with some clinical features related to adenoma in patients with acromegaly.
Keywords: Acromegaly; single nucleotide polymorphism; HMGA2; AIP; miRNA; somatostatin analogue